The Application of the RADEC Learning Model to the Speaking Skills of V Grade Elementary School Students with Audiovisual Media on the Theme of Humans and the Environment - Nuraeni, Ayu; Maftuh, Bunyamin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Communicating is used to build and maintain relationships with other people. The 2013 curriculum emphasizes the importance of 21st century skills, namely 4C: communication, collaboration, critical thinking and problem solving, and creativity and innovation. The Read, Answer, Discuss, Explain, and Create (RADEC) learning model is a learning model that is capable of encouraging students to develop 21st century skills and to master the learning concepts which are being learnt. The formulation of the research problem is how to apply the read answer discuss explain and create learning model to the speaking skills of fifth grade elementary school students using audiovisual media on the theme of humans and the environment. The purpose of the study is to find out how to apply the read answer discuss explain and create learning model to the speaking skills of fifth grade elementary school students with audiovisual media on the theme of humans and the environment. The research was conducted at Pasindangan Elementary School, Gunung Jati District, Cirebon Regency. The number of students was 13 people. The construction of the research results is analyzed using a qualitative descriptive approach. The data was obtained from rubric assessment and observation. The results of the study are based on six aspects of speaking, namely: pronunciation; 31%, language structure; 46%, vocabulary; 38%, fluency; 38%, the content of the conversation; 31%, understanding; 15%. Hence from these results, it is established that learning with the application of the RADEC model using audiovisual media on the theme of humans and the environment can improve students' speaking skills.